Orienting attention to auditory and visual working memory in older adults with cochlear implants. - Amisha Ojha; Andrew Dimitrijevic; Claude Alain (PLoS ONE)
Cochlear implantation is a well-established method for restoring hearing sensation in individuals with severe to profound hearing loss. It significantly improves verbal communication for many users, despite substantial variability in patients' reports and performance on speech perception tests and quality-of-life outcome measures. Such variability in outcome measures remains several years after implantation and could reflect difficulties in attentional regulation. The current study assessed the ability to use a cue to guide attention internally toward visual or auditory working memory (i.e., reflective attention) in cochlear implant (CI) users. Participants completed a cognitive task called the delayed match-to-sample task in which a visual gradient was presented on a computer screen and a piano tone was presented through speakers simultaneously. A visual cue (i.e., letter A or V) instructed participants to focus attention on the item held in auditory or visual working memory. After a delay following the cue presentation, participants were presented with a probe item and indicated by pressing a button whether it matched the cued item in working memory. CI users and age-matched normal hearing adults showed comparable benefit from having an informative cue relative to an uninformative cue (i.e., letter X). Although CI users have had a history of severe deafness and experience coarse sound information, they were able to retrospectively orient their attention to an item in auditory or visual working memory. These findings suggest that CI users with at least one year of CI experience can successfully regulate attention to a level that is comparable to that of normal hearing individuals.